Analisis Penggunaan Platform Kolaborasi Digital oleh Mahasiswa untuk Manajemen Arsip Tugas Perkuliahan - Syandana , Tatsbita Moza; Hidayah, Ma’rifatul; Pramono, Nadine Keyshya; Kinanthi, Nayla Dinar; Patria, Niken Aiko; Pramida, Qesya Aurelia; Frastyawan, Raffi Bima (Jurnal Portofolio : Jurnal Manajemen dan Bisnis, 2026)
This study aims to analyze the use of digital collaboration platforms by university students in managing academic assignment archives. The rapid development of information technology has encouraged students to utilize various digital platforms such as Google Drive, Microsoft Teams, WhatsApp, and Learning Management Systems (LMS) for storing, organizing, and collaborating on academic documents. This research employs a quantitative method with a descriptive approach, using data collected through questionnaires based on a five-point Likert scale. The respondents are students of the Records and Archives Management Program at Universitas Indonesia who have experience using digital collaboration platforms in academic activities. The analysis focuses on three main dimensions: Man (users), Money (cost), and Method (working methods). The results indicate that the Man and Method dimensions achieve high mean scores, suggesting that students perceive digital platforms as easy to use, functionally beneficial, and efficient for managing academic assignment archives. Meanwhile, the Money dimension shows that internet costs remain a consideration but do not constitute a major barrier to the adoption of digital collaboration platforms. This study concludes that digital collaboration platforms have a positive impact on the organization, efficiency, and collaboration of students in managing academic archives, although improvements in digital archival literacy are still needed to reduce archival management errors.